Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3748/wjg.v28.i1.96
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hepatocellular carcinoma after hepatitis C virus cure

Abstract: Hepatitis C virus (HCV) is a significant cause of hepatocellular carcinoma (HCC). The direct-acting antivirals marked a new era of HCV therapy and are associated with greater than 95% cure rate. Successful treatment of chronic hepatitis C greatly reduces the risk of HCC. A proportion of patients, especially those with pre-existing cirrhosis, remain at risk for HCC despite sustained virologic response (SVR). Diabetes mellitus, hepatic steatosis, alcohol consumption and lack of fibrosis regression are associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 73 publications
2
15
0
Order By: Relevance
“…However, in patients with cirrhosis, the risk of HCC persists even after HCV treatment. The number of patients with cirrhosis who have been cured of HCV is predicted to increase in the future [55]. Owing to dysregulated host factors during HCV infection, these patients are still at risk for liver disease development.…”
Section: Discussionmentioning
confidence: 99%
“…However, in patients with cirrhosis, the risk of HCC persists even after HCV treatment. The number of patients with cirrhosis who have been cured of HCV is predicted to increase in the future [55]. Owing to dysregulated host factors during HCV infection, these patients are still at risk for liver disease development.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic HCV infection has been found as major cause of hepatocellular carcinoma. The occurrence and reoccurrence of HCC in HCV patients receiving DAAs therapy has sparked a large debate ( Tayyab et al, 2020 , Ogawa et al, 2020 , Luna-Cuadros et al, 2022 ). The clinical studies have shown that the DAAs therapy is an effective tool in reducing the risk of HCC development in cirrhotic HCV patients, however, it cannot eradicate the risk of HCC recurrence permanently ( Singer et al, 2018 , Singh et al, 2018 , Ioannou et al, 2018 , Nakano et al, 2019 , Pons et al, 2020 , Dang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The DDAs alone or in combination of other drugs have increased the SVR up to 90 percent and decreased the treatment duration up to 12 weeks ( Asselah et al, 2016 ). Debate has been emerging about the occurrence and recurrence of hepatocellular carcinoma in HCV patients receiving DAAs therapy ( Tayyab et al, 2020 , Ogawa et al, 2020 , Luna-Cuadros et al, 2022 ). Over the time, a series of clinical studies reported the efficacy of DAAs therapy in reducing the risk of HCC development in cirrhotic HCV patients.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these mechanisms may persist even after HCV eradication, and thus the risk of HCC development is not abolished. This is still a hotly discussed subject [ 154 , 161 ].…”
Section: Hcc Related To Specific Diseasesmentioning
confidence: 99%